Bullying and harassment – Are junior doctors always the victims?. Issue 4 (November 2016) - Nyhsen, C.M.; Patel, P.; O'Connell, J.E.
Abstract: Introduction: NHS staff have the right to work in an environment free from bullying, harassment and violence. There should be good team-working with colleagues from all disciplines. Reports of bullying experienced by junior doctors resulted in mandatory annual GMC surveys regarding the quality of training. This led to medical trainees being surveyed more than any other staff. Radiographers informally reported bullying and harassment (B&H) incidents involving trainees. This survey aims to quantify the issue. Methods: Online survey of general and CT radiographers at a large acute hospital in the North East of England addressing incidents involving junior doctors and occurring in the preceding 12 months. Results: The survey was completed by 86% (44/51) general and 5/7 CT radiographers. Overall 45% experienced bullying, 92% had their own/witnessed a colleague's opinion being ignored and 57% were the target of loud verbal abuse/anger or witnessed colleagues being treated in that way. Several radiographers reported 5 or more B&H incidents. 26 radiographers (51%) were shouted at/ridiculed in theatre, 4 feeling unsafe/physically threatened. Junior doctors regularly queried the need to supervise CT contrast injections on call. Free text comments highlighted that doctors rarely introduced themselves to radiology staff. Conclusion: Radiographers report significant incidents of B&H involving junior doctors, who do not always seem to appreciate radiation exposure legislation, patient safety protocols or respect the seniority of highly trained radiographers. Measures introduced subsequently include guidance for radiographers, a dedicated radiology e-learning package for trainees and classroom sessions for foundation doctors and final year undergraduate students. Highlights: Bullying and harassment of radiographers is a persistent problem. Some radiographers reported feeling physically threatened in theatre. Some junior doctors do not respect radiation exposure legislation/safety protocols. Many junior doctors do not introduce themselves to radiology staff. Junior doctor e-learning and classroom sessions were introduced to address issues.